Das Nivellement über das grönländische Indlandeis der Internationalen Glaziologoschen Grönland-Expedition 1959. - Mälzer, H. (Meddelelser om Grønland, 1964)
During the Summer Campaign 1959 of EGIG, the geometrical levelling was used for the first time in arctic zones to obtain an accurate carrying of the heights over large distances. Within nearly 3 months a profile of almost 700 km length was levelled from the western shore of middle Greenland in eastern direction across the inland ice. The inner precision of the levelling for this profile exceeds the demands of the glaciology and geophysic. The levelling had to be stopped at the wintering station of Jarl-Joset, 250 km to the southwest of Cecilia Nunatak, the end of the profile. Control was established by independent double measurements. The results are the differences of elevation between the ablation level points of the western part of the profile and between the balises (bench marks) on the icecape, the elevation of these points and an accurate profile of the heights.